506 Samelisant: Baseline Characteristics from a Phase 2 Study Evaluating Efficacy and Safety in Patients with Narcolepsy. (3rd May 2021) - Nirogi, Ramakrishna; Ravula, Jyothsna; Jayarajan, Pradeep; Jetta, Satish; Bhyrapuneni, Gopinadh; Benade, Vijay; Shinde, Anil; Goyal, Vinod
Abstract: Introduction: histamine H3 receptor (H3R) antagonists/ inverse agonists increase histaminergic neurotransmission and offer a therapeutic option for the treatment of narcolepsy. Samelisant (SUVN-G3031) is a potent and selective H3R inverse agonist exhibited selectivity over 70 other targets. Samelisant showed wake-promoting and anticataplectic effects in orexin knockout mice suggesting its potential therapeutic utility in the treatment of EDS and cataplexy associated with narcolepsy. Safety and tolerability studies in animals and healthy humans suggested a favorable risk/benefit profile. Methods: The current study is a 2 week treatment, multicenter, double-blind, placebo controlled, parallel-group study in patients with Narcolepsy with or without Cataplexy. Eligibility criteria include age between 18 to 50 years old, an ESS score of ≥ 12; and mean MWT time of < 12 minutes and a confirm diagnosis of narcolepsy as per ICSD-3. Further, the randomization will be stratified according to type of narcolepsy (Type-1 or Type-2). Each subject will receive either placebo or study drug once daily for 2 weeks in a fixed ratio of 1:1:1. The primary efficacy endpoint is change in maintenance of wakefulness test (MWT) score from baseline to week 2. Key secondary endpoints include change from baseline to week 2 in ESS and an improvement in CGI-S scores. Safety will be monitored by medical monitor and by an independent data safety monitoring committee. Baseline clinical and demographic data for the currently enrolled study is summarized descriptively. Since the study is blinded, a breakdown of baseline characteristics by treatment group will not be available until after completion. Results: As of data cutoff date of Dec 20, 2020, a total of 54 subjects were completed in the study. The median age of subjects was 30 years (range: 18 - 50 years) with mean BMI of 28.6 (range: 18.3 - 43.1 kg/m2). Overall, 74% of subjects were female and 83% were Caucasian. Mean (SD) baseline values of MWT and ESS are 5.65 (3.5) and 16.7 (2.5), respectively. Conclusion: Baseline characteristics are consistent with the general narcolepsy population. The study is currently enrolling the subjects with Narcolepsy with or without Cataplexy, and the Data readout is expected in the second half of 2021. Support (if any):